A Sociocultural Investigation of the Preservation and Resilience of Baluchi Culture Amid Modernization in The Wandering Falcon - Khalid, Alina; Riaz, Raj Kanwal; Nasir, Muhammad Saeed (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
The paper explores the tension between tradition and transformation within Baluchi culture as it confronts the force of modernization. The present paper also explores the preservation and the resilience of Baluch cultural practices through the lenses of diaspora theory and cultural identity, particularly in the context of modernization through the narrative The Wandering Falcon, written by Jamil Ahmad and published in 2011. Despite external pressures, the Baluch people uphold their way of living such as tribal revenge customs, the significance of lineage, symbolic attire, leadership structures, and the practice of bride price. These cultural elements serve as anchors of identity, enabling Baluch communities to navigate and adapt to changing milieus while preserving their distinctive heritage. The analysis highlights the dynamic interplay between cultural preservation and adaptation, demonstrating the Baluch community’s commitment to sustaining their cultural identity amidst global influences.